Why is $\arctan\frac{x+y}{1-xy} = \arctan x +\arctan y$?

It is said that this is derived from trigonometry, but I couldn't find why this is the case.

  • 7
    Remember that : $$\tan(a+b)=\frac{\tan a + \tan b}{1-\tan a \tan b}.$$ – user37238 Sep 23 '13 at 7:35
  • 4
    This is not quite true. What is true is that $\tan(s+t)=\frac{\tan s+\tan t}{1-\tan s\tan t}$. The reason the $\arctan$ version can fail is because of restrictions on the range of $\arctan$. But it is true, for example, when $0\le x,y\lt \frac{\pi}{4}$. – André Nicolas Sep 23 '13 at 7:38
  • Because they are the same number :p – Alephnull Aug 6 '16 at 17:00
up vote 11 down vote accepted

Here's a proof that has essentially nothing to do with trigonometry:

Hold $y$ constant and differentiate the function $$f(x) = \arctan{\frac{x + y}{1 - xy}} - \arctan{x} - \arctan{y}$$ to find that

\begin{align}f'(x) &= \frac{1}{1 + \left(\frac{x + y}{1 - xy}\right)^2} \cdot \left(\frac{(1 - xy) - (x + y)(-y)}{(1 - xy)^2}\right) - \frac{1}{1 + x^2} \\ &= \frac{(1 - xy)^2}{(1 - xy)^2 + (x + y)^2} \cdot \left(\frac{1 - xy + xy + y^2}{(1 - xy)^2}\right) - \frac{1}{1 + x^2} \\ &= \frac{1 + y^2}{1 - 2xy + x^2y^2 + x^2 + 2xy + y^2} - \frac{1}{1 + x^2} \\ &= \frac{1 + y^2}{1 + x^2 + y^2 + x^2y^2} - \frac{1}{1 + x^2} \\ &= \frac{1 + y^2}{(1 + y^2) + x^2 (1 + y^2)} - \frac{1}{1 + x^2} \\ &= \frac{1}{1 + x^2} - \frac{1}{1 + x^2} = 0 \end{align}

So $f$ is a constant. Letting $x = 0$, we find that $f(0) = 0$ and the identity follows.

  • 1
    This is indeed true for $\mid xy \mid <1$, thats why you can take $x=0$. But what if we have $\mid xy \mid>1$? Then you should take some x so that it is always true and you should get $f(0)=-\pi$. – HeatTheIce Jan 20 '16 at 16:49

The following identity is useful for your purpose

$$ \tan(\alpha \pm \beta) = \frac{\tan \alpha \pm \tan \beta}{1 \mp \tan \alpha \tan \beta}. $$

To prove it just use the identity $ \tan(t) = \frac{\sin(t)}{\cos(t)}$ and the identities for $\sin(a\pm b)$ and $\cos(a\pm b)$.

Do NOT blindly use this for calculations. Example $\arctan(5000)+\arctan(5000) \sim \pi/2+\pi/2=\pi$ with the formula quoted you get $\arctan(10000/(1-25\times10^6))\sim\arctan(-1/2500)\sim~0$. Like Andre Nicolas said, you need to considr arctan ranges

Computing with complex numbers: $$ (1+xi)(1+yi)=(1-xy)+(x+y)i $$ Take arg on both sides $$ \arctan x + \arctan y = \arg(1+xi)+\arg(1+yi) = \arg((1+xi)(1+yi)) \\ = \arg((1-xy)+(x+y)i) = \arctan\frac{x+y}{1-xy} $$

  • A very illuminating approach. Most trig relationships can be trivially derived using the Euler's identity and cartesian to polar conversion like this. – orion Oct 3 at 12:15

Ok fine, mlc. I'll answer the question. Here is a trigonometric proof. No calculus required. Statement: $\arctan(\frac {x+y} {1-xy})=\arctan(x)+\arctan(y)$ whenever $|xy|<1$.

Proof. Choose $(x,y)\in\big\{|xy|<1\big\}$ arbitrarily. This formula is obvious if $x=0,$ so first consider when $x>0$. We prove that $\arctan(x)+\arctan(y)\in\Big(\frac{-\pi}{2},\frac{\pi}{2}\Big)$. Note $|xy|<1$ if and only if $-\frac{1}{x}<y<\frac1x$. Since $\arctan$ is an increasing and odd function, it follows $$-\arctan\Big(\frac{1}{x}\Big)<\arctan(y)<\arctan\Big(\frac{1}{x}\Big).$$ Indeed, $\arctan(x)+\arctan(\frac{1}{x})=\frac{\pi}{2},$ and so $$-\frac\pi2<2\arctan(x)-\frac\pi2<\arctan(x)+\arctan(y)<\frac\pi2.$$ This shows $\arctan(x)+\arctan(y)$ belongs to the range of $\arctan$, $\Big(\frac{-\pi}{2},\frac{\pi}{2}\Big)$. The angle sum identity tells us $$\begin{equation}\begin{split}\tan(\arctan(x)+\arctan(y)) &=\frac{\tan(\arctan(x))+\tan(\arctan(y))}{1-\tan(\arctan(x))\tan(\arctan(y))} \\ & =\frac{x+y}{1-xy}\end{split}\end{equation}$$

Hence $$\begin{equation}\begin{split}\arctan(x)+\arctan(y)&=\arctan(\tan(\arctan(x)+\arctan(y))) \\ &=\arctan\Big(\frac{x+y}{1-xy}\Big)\end{split}\end{equation}$$ This proves the identity for $x>0,$ so now assume $x<0$. Then $-x>0$ and $|xy|<1$ $\iff$ $-\frac{1}{x}<-y<\frac{1}{x}.$ Finally, $$\begin{equation}\begin{split}\arctan(x)+\arctan(y) & =-\big(\arctan(-x)+\arctan(-y)\big) \\ & =-\arctan\Big(\frac{-x-y}{1-(-x)(-y)}\Big) \\ & =\arctan\Big(\frac{x+y}{1-xy}\Big)\end{split}\end{equation}$$ The result follows.

Consider $$A=\arctan(x)+\arctan(y),$$ then $$\tan(A)=\tan(\arctan(x)+\arctan(y)),$$ which is also equal to:$$\frac{\tan(\arctan(x))+\tan(\arctan(x))}{1-\tan(\arctan(x)) + \tan(\arctan(y)},$$ which simplifies to giv:$$\tan(A)=\frac{x+y}{1-xy}.$$


Your Answer


By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.